2020
DOI: 10.3168/jds.2019-17735
|View full text |Cite
|
Sign up to set email alerts
|

Localization of aquaporin-3 proteins in the bovine rumen

Abstract: Urea nitrogen salvaging is a crucial mechanism that ruminants have evolved to conserve nitrogen. Facilitative urea transporter-B proteins are known to be involved in urea transport across the rumen epithelium and thus efficiently facilitate the urea nitrogen salvaging process. Recently, functional studies have suggested that aquaglyceroporin transporters might also play a significant role in ruminal urea transport and aquaporin-3 (AQP3) protein has previously been detected in rumen tissue. In this current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
9
2
Order By: Relevance
“…+ can be assumed. The finding that complex proteins are required to mediate ruminal transport not only of urea [50,65] but also of ammonium across the ruminal wall should end the concept of ruminal nitrogen recycling as the result of a "leaky" epithelium. Instead, nitrogen recycling appears an efficient mechanism to remove protons from the rumen with the energy coming from the liver (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…+ can be assumed. The finding that complex proteins are required to mediate ruminal transport not only of urea [50,65] but also of ammonium across the ruminal wall should end the concept of ruminal nitrogen recycling as the result of a "leaky" epithelium. Instead, nitrogen recycling appears an efficient mechanism to remove protons from the rumen with the energy coming from the liver (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, a clarification of the mechanism responsible for the high efflux of ammonia from the rumen is overdue. The expression profile in the ovine rumen does not appear to support the involvement of either RhCG or RhCB [65]. Systematic studies of ruminal transport of ammonia have established that electroneutral transport of NH 3 is predominant at an alkaline pH of 7.4.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, a revealing functional study by Walpole and colleagues suggested a potential role in ruminal urea transport for aquaglyceroporins, such as AQP3 [10]. After AQP3 protein was first identified in the rumen [16], it has recently been demonstrated that ruminal AQP3 RNA levels are regulated by diet [17] and that two distinct AQP3 proteins may localize to various layers of cow rumen papillae [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both K + channels [ 19 ] and K + transporters such as NKCC [ 50 ] can transport NH 4 + , which is not surprising since the biophysical properties of both ions are similar. Functional data from in vitro studies of the ruminal epithelium show that at an unphysiologically high pH of 7.4, absorption of ammonia involves diffusion of NH 3 [ 3 ]—possibly via AQP3 [ 120 ] since Rh glycoproteins do not appear to be expressed [ 119 ]. However, at the more physiological pH of ~ 6.4 found in vivo, uptake of NH 4 + clearly predominates [ 3 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%